Complex dynamics in a simple model of interdependent open economies - Shahriar Yousef; Yuri Maistrenko; Svitlana Popovych (Discrete Dynamics in Nature and Society)
Based on a simple two-market model, characterized by a demand link between competitive markets for goods, a system of coupled difference equations is used to represent the interdependent structure of a global economy. Relying on numerical and analytical approaches, Various dynamic properties of the proposed model are explored. Among others, a general specification of the regions of stability of the equilibrium and main periodic cycles, the transition to chaos through torus destruction, chaotic synchronization, and the coexistence of different types of attractors in parameter space are described. Typical bifurcation processes are illustrated.